The Effect of Readiness of MSMEs Actors, Human Resource Potential, and Accounting Understanding on the Implementation of SAK EMKM - Bintang Nur Hakim; Ridwan Ridwan (eCo-Buss, 2024)
In this study, the human resource competency, accounting knowledge, and readiness of micro, small, and medium-sized enterprise (MSME) actors in Bandung Kidul District, Bandung City, are investigated to see how they influence the implementation of SAK EMKM. Quantitative methods were utilised to administer surveys to 115 MSME participants participating in SAK EMKM. During the data analysis process, validation, reliability, normalcy, multicollinearity, t-tests, and F-tests were all included in the considerations. The results indicate that the human resource competency, accounting knowledge, and preparedness of MSME actors significantly impact the implementation of SAK EMKM and that this impact is partially simultaneous. More specifically, the t-count for accounting understanding was 3.410, the t-count for human resource competency was 4.957, and the t-count for MSME actor preparedness was 2.540, with a significance level of 0.012. It was determined that the regression model generated a significant F-count of 27.332 when the significance threshold was set at 0.000. To improve the execution of SAK EMKM, it is essential to strengthen the preparation of MSME players, as well as their competence in human resources and their awareness of accounting rules. According to the study's findings, participants in the MSME sector ought to be provided with specialised training and resources to enable them to improve their financial reporting and conform to the standards presented by SAK EMKM. By addressing these challenges, micro, small, and medium-sized enterprises (MSMEs) may be able to adhere to financial standards with greater ease, which will ultimately assist both their expansion and the broader economic development of the district of Bandung Kidul.